2006
DOI: 10.1002/ca.20284
|View full text |Cite
|
Sign up to set email alerts
|

An unusual innervation of pectoralis minor and major muscles from a branch of the intercostobrachial nerve

Abstract: Variations of the branching pattern of the intercostobrachial nerve have been known to complicate dissection during mastectomy and other procedures involving the axilla. We present a unilateral case of a 73-year-old Caucasian female, in which the intercostobrachial nerve gives rise to an additional medial pectoral branch, which partially innervates the pectoralis minor muscle, as well as the abdominal head of pectoralis major muscle. Clinical consequences of such a variation may include motor losses, in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Some authors had also previously described cases in which the intercostobrachial nerve penetrated the pectoralis major and minor muscles without innervating them (Cunnick et al,2001; Freeman et al,2003). The possible presence of motor nerve fibers for the pectoral muscles in the intercostobrachial nerve further supports the importance of its preservation during axillary surgical procedures (Loukas et al,2006b, 2007). Anastomosis has also been observed between the LPN and the subclavius nerve (Hovelacque,1927).…”
Section: Sensory Innervation and Connections With Other Nervesmentioning
confidence: 70%
See 1 more Smart Citation
“…Some authors had also previously described cases in which the intercostobrachial nerve penetrated the pectoralis major and minor muscles without innervating them (Cunnick et al,2001; Freeman et al,2003). The possible presence of motor nerve fibers for the pectoral muscles in the intercostobrachial nerve further supports the importance of its preservation during axillary surgical procedures (Loukas et al,2006b, 2007). Anastomosis has also been observed between the LPN and the subclavius nerve (Hovelacque,1927).…”
Section: Sensory Innervation and Connections With Other Nervesmentioning
confidence: 70%
“…Although this kind of communication was not confirmed in a more recent article (Loukas et al,2006c), other kinds of relationships with the PNs and muscles were described. In a case report, an additional medial pectoral branch, partially innervating the pectoralis minor muscle as well as the abdominal head of the pectoralis major muscle was seen arising from the intercostobrachial nerve (Loukas et al,2006b). In another case, the intercostobrachial nerve has been described to directly receive a branch from the MPN, which partially innervated the pectoralis major and minor muscles (Loukas et al,2007).…”
Section: Sensory Innervation and Connections With Other Nervesmentioning
confidence: 99%
“…It may receive contributions from other intercostal branches (T1, T3, and even T4) and can have a variety of anastomoses with branches of the brachial plexus, including the medial antebrachial cutaneous nerve, posterior cutaneous nerve of the forearm, and rarely with the pectoral nerves. [23][24][25] This nerve is often implicated in postmastectomy pain, particularly after axillary dissection or lymph node sampling. 26,27 Its variable anatomy may account for the conflicting reports of post-nerve injury symptoms.…”
Section: Innervation Of the Breast And Superficial Tissuesmentioning
confidence: 99%
“…A case report describes a variation of the branching pattern of the ICBN where the nerve gives rise to an additional medial pectoral branch, which has partial motor innervation to the pectoralis minor muscle and abdominal head of the pectoralis major muscle. Injuries to the ICBN with these variants can thus give rise to further motor losses in addition to typically reported sensory only paresthesias involved in intercostobrachial neuralgia [9]. In another study of 100 adult human cadavers, researchers examined the variants of ICBN and found 8 main variants of the ICBN, including a variant describing the ICBN arising from T2 and giving off a branch to the brachial plexus, and a less‐common variant in which lateral cutaneous branches of T2 and T3 fuse as a common trunk then split after exiting the intercostal space to form an ICBN [3].…”
Section: Discussionmentioning
confidence: 99%